8-isoprostane and leukotrienes in exhaled breath condensate in Czech subjects with silicosis - Pelclová, Daniela; Fenclová, Zdenka; Kacer, Petr; Navrátil, Tomá; Kuzma, Marek; Lebedová, Jindri Ka; Klusácková, Pavlína (Industrial health, 2007)
Silicosis has progressive, but unpredictable development. There are no markers routinely available to measure the activity and prognosis of silicosis. 8-isoprostane, a marker of oxidative stress and leukotrienes B4, C4, D4, and E4 were measured in exhaled breath condensate in patients with silicosis. Sixty subjects were examined, with mean age 66.7+/-2.0 yr and mean exposure to silica 23.6+/-2.5 yr. The control group had 25 subjects, with mean age 64.7+/-4.8 yr. Exhaled breath was collected using the EcoScreen (Jaeger, Germany); 8-isoprostane and leukotrienes were analyzed by high-performance liquid chromatography/mass spectrometry. Several lung functions parameters were impaired in silicotics in comparisons with the controls; ESR, alpha1-antitrypsin and proteinuria were higher in the silicotics. Antineutrophilic cytoplasmic antibodies were more frequent in the silicotics (39%) than in the controls (4%), (p=0.0017). The mean level of 8-isoprostane in the patients with silicosis was 73.6+/-9.9 vs. 43+/-10 pg/ml (p=0.0001) in the controls. Silica exposure category (high, medium, none) was positively associated with the level of 8-isoprostane. In the patients with complicated silicosis, a high level of 8-isoprostane was found more frequently (p=0.0194). Leukotriene D4 was also increased in the silicotics (21.1+/-2.7 pg/ml) vs. the controls (14.7+/-2.7 pg/ml), (p=0.001). No significant effect of smoking or alcohol consumption on the markers examined was seen. This is the first study using exhaled breath condensate analysis in patients with silicosis.
Keywords: Female; Leukotrienes; biologické markery; Biomarkers; ženské pohlaví; vysokoúčinná kapalinová chromatografie; Time Factors; časové faktory; lidé; Breath Tests; dinoprost; hmotnostní spektrometrie; Humans; leukotrieny; zdravé chování; Chromatography, High Pressure Liquid; Male; Aged; Czech Republic; silikóza; Mass Spectrometry; Česká republika; Dinoprost; lidé středního věku; dechové testy; Respiratory Function Tests; senioři; mužské pohlaví; respirační funkční testy; Middle Aged; Silicosis; Health Behavior